2022
DOI: 10.3390/antibiotics11111602
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Patient-Reported Outcomes Measures and Quality-Adjusted Life Years Following One- and Two-Stage Septic Knee Exchange

Abstract: (1) Background: Periprosthetic joint infection (PJI) can be managed with one- or two-stage revision surgery protocol. Despite several studies analyzing the eradication rates between both procedures, there are no comparative studies that analyze patient-reported outcome measures (PROMs) and quality-adjusted life years (QALYs) in both treatment strategies. (2) Methods: All patients who underwent a two-stage knee revision between January 2017 to December 2018, due to a periprosthetic joint infection were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…A previous meta-analysis with aggregated data showed there is no difference in re-infection rates between one-stage and two-stage revisions [7]. Smaller studies also suggest there is no difference in patient-reported outcomes and Knee Society functional scores [8,9]. However, two-stage revisions are preferred by members of the American Association of Hip and Knee Surgeons (AAHKS) when treating PJIs [10].…”
Section: Introductionmentioning
confidence: 99%
“…A previous meta-analysis with aggregated data showed there is no difference in re-infection rates between one-stage and two-stage revisions [7]. Smaller studies also suggest there is no difference in patient-reported outcomes and Knee Society functional scores [8,9]. However, two-stage revisions are preferred by members of the American Association of Hip and Knee Surgeons (AAHKS) when treating PJIs [10].…”
Section: Introductionmentioning
confidence: 99%